Rapid seedling emergence of invasive Phytolacca americana is related to higher soluble sugars produced by starch metabolism and photosynthesis compared to native P. acinosa - Liu, Danfeng; Liu, Maoye; Ju, Ruiting; Li, Bo; Wang, Yi (Frontiers in Plant Science, 2024)
Seedling emergence is an essential event in the life cycle of plants. Most invasive plants have an advantage in population colonization over native congeners. However, differential seedling emergence between invasive plants and native congeners, especially their mechanisms, have rarely been explored. In this study, we show that the seedlings of invasive Phytolacca americana emerge faster compared to native P. acinosa. Genome-wide transcriptomes of initially germinated seeds versus seedlings at 4 days after germination (DAG) suggested that differentially expressed genes (DEGs) in the photosynthesis-antenna proteins pathway were up-regulated in both P. americana and P. acinosa, while DEGs in starch and sucrose metabolism were significantly downregulated in P. americana. Gene expression analysis indicated that photosynthesisrelated DEGs reached their highest level at 3 DAG in P. americana, while they peaked at 4 DAG in P. acinosa. We also identified one β-amylase gene in P. americana (PameAMYB) that showed the highest expression at 1 DAG, and two β-amylase genes in P. acinosa that expressed lower than PameAMYB at 0 and 1 DAG. Enzymatic activity of β-amylases also suggested that P. americana had the highest activity at 1 DAG, which was earlier than P. acinosa (at 4 DAG). Soluble sugars, the main source of energy for seedling emergence, were showed higher in P. americana than in P. acinosa, and reached the highest at 4 DAG that positively affected by photosynthesis. These results indicate that the rapid seedling emergence of invasive P. americana benefited from the high soluble sugar content produced by starch metabolism and photosynthesis.Altogether, this work contributes to our fundamental knowledge on physiological and molecular mechanisms for plant invasion success.